In vitro analysis with human bone marrow stem cells on Ti-15Mo alloy for dental and orthopedic implants application - N.T.C. Oliveira; V. Perrott; A. Palmieri; A.C. Guastaldi; A. Pellati; C.L. Scapin; A. Piattelli; F. Carinci (Ariesdue, 2011)
Aim: Nowadays, research on orthopedic and dental implants is focused on titanium alloys for their mechanical properties and corrosion resistance in the human body environment. Another important aspect to be investigated is their surface topography, which is very important to osseointegration. With laser beam irradiation for roughening the implants surface an easier control of the microtopography is achieved, and surface contamination is avoided. The aim of this study was to assess human bone marrow stem cells response to a newly developed titanium alloy, Ti-15Mo, with surface topography modified by laser beam irradiation. Materials and methods: A total of 10 Ti machined disks (control), 10 Ti-15Mo machined disks and 10 Ti-15Mo disks treated by laser beam-irradiation were prepared. To study how Ti-15Mo surface topografy can induce osteoblast differentiation in mesenchymal stem cells, the expression levels of bone related genes and mesenchymal stem cells marker were analyzed, using real time Reverse Transcription-Polymerase Chain Reaction. Results: In Test 1 (comparison between Ti-15Mo machined disks and Ti-machined disks) quantitative real-time RT-PCR showed a significant induction of ALPL, FOSL1 and SPP1, which increase 20% or more. In Test 2 (comparison between Ti-15Mo laser treated disks and Ti-machined disks) all investigated genes were up-regulated. By comparing Test 1 and Test 2 it was detected that COL1A1, COL3A1, FOSL1 and ENG sensibly increased their expression whereas RUNX2, ALPL and SPP1 expression remained substantially unchanged. Conclusion: The present study demonstrated that laser treated Ti-15Mo alloys are promising materials for implants application.